Double C Clamp : Powerful Solution for High Pressure Air-Fin Cooler Hexagonal Tube Plugs - Situmorang, Indra Harapan; Jhonem, Akbar Putra; Hermawan, Rudi; Taufan, Edward Cantona; Zulfajri (Syntax Literate, 2026)
Hydrocracker reliability has a direct effect on refinery margin, product availability, and process safety. This paper presents an industrial case study on the development and implementation of an online leak sealing (OLS) innovation for a leaking hexagonal plug in the fresh feed reactor effluent air cooler (REAC) 211 E-2D at the Hydrocracker Unit (HCU) of PT Pertamina Patra Niaga RU II Dumai. During hydrocracker recovery in April 2023, a leak was detected at plug tube No. 19 Bank D under hydrocarbon service containing 85-90% hydrogen, at approximately 170 kg/cm2 and 150 C. Conventional hot bolting did not stop the leak and plant procedures indicated that shutdown would normally be required. To prevent unscheduled shutdown, a high-pressure double-C clamp combined with OLS was designed, stress-checked, fabricated, and installed onstream. The new design increased clamp pressure capability from the 34 kg/cm2 reference design to 250 kg/cm2 and could accommodate multiple leak points. Post-installation monitoring showed 0% LEL around the leak area, the unit operated normally for more than five months, and a 13-day shutdown was avoided. Operational records indicated margin protection of IDR 1.9 billion and additional protected value from valuable products and HVGO lifting opportunities. The case demonstrates that a properly engineered OLS system can be a practical reliability and safety solution for hydroprocessing air coolers with hexagonal plug leakage.